Herpesviruses: Harmonious Pathogens but Relevant Cofactors in Other Diseases? - Sehrawat, Sharvan; Kumar, Dhaneshwar; Rouse, Barry T. (Frontiers in Cellular and Infection Microbiology, 2018)
Most vertebrates are infected with one or more herpesviruses and remain so for the rest of their life. The relationship of immunocompetent healthy host with herpesviruses may sometime be considered as harmonious. However, clinically severe diseases can occur when host immunity is compromised due to aging, during some stress response, co-infections or during neoplastic disease conditions. Discord can also occur during iatrogenic immunosuppression used for controlling graft rejection, in some primary genetic immunodeficiencies as well as when the virus infects a non-native host. In this review, we discuss such issues and their influence on host-herpesvirus interaction.